2002
DOI: 10.1785/gssrl.73.5.660
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the Earthquake Source of the Wabash Valley Seismic Zone (Illinois, Indiana, and Kentucky) from Seismic-reflection, Gravity, and Magnetic-intensity Data

Abstract: Reprocessing of seismic-reflection data reveals new images of upper-to middle-crustal structures beneath the Wabash Valley seismic zone, located north of the New Madrid seismic zone within the seismically active southern Illinois basin. Four intersecting deep seismic profiles (243 km total) indicate an anomalous, 5-10-km-wide zone of dipping reflections and diffractions below the western flank of the Wabash Valley fault system (WVFS). The zone corresponds in places to gently arched regions of Paleozoic strata.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Langenheim and Hildenbrand (1997) estimated that the CGL is 20-40 km wide; we use 30 km. McBride et al (2002) used deep seismicreflection profiles to estimate a width of 5-10 km for the inferred fault system that underlies the CGL southwest of the Vincennes bend. However, if the bend has been acting as a restraining bend for many earthquake cycles, the resulting network of reverse, right-lateral, and oblique-slip faults might have broadened as deformation proceeded.…”
Section: Commerce Geophysical Lineamentmentioning
confidence: 99%
“…Langenheim and Hildenbrand (1997) estimated that the CGL is 20-40 km wide; we use 30 km. McBride et al (2002) used deep seismicreflection profiles to estimate a width of 5-10 km for the inferred fault system that underlies the CGL southwest of the Vincennes bend. However, if the bend has been acting as a restraining bend for many earthquake cycles, the resulting network of reverse, right-lateral, and oblique-slip faults might have broadened as deformation proceeded.…”
Section: Commerce Geophysical Lineamentmentioning
confidence: 99%
“…This parallelism has been suggested to be evidence for a structural relation between the two anomalies (Langenheim and Hildenbrand, 1997;Stephenson et al, 1999). Based on potential-field models and seismic-reflection data, McBride et al (2002) describe the source of the CGL in the southern Illinois basin as a strongly deformed Precambrian feature, approximately 5-10 km wide. modeled magnetic and gravity data for the Illinois basin and concluded that the source of the CGL follows the southeastern boundary of a dense and magnetic, northeasttrending igneous complex.…”
Section: Commerce Geophysical Lineamentmentioning
confidence: 99%
“…1), which consists of a network of northeast-southwesttrending faults (Ault and Sullivan, 1982;Ault et al, 1985;Rene and Stanonis, 1995;Woolery, 2005). The faults were first discovered by petroleum exploration drilling in the early 1900s and were then widely studied by geological and geophysical investigations (Pratt et al, 1992;McBride et al, 2002;Duchek et al, 2004;McBride et al, 2007). Previous studies suggested that those faults were high-angle normal faults that formed in late Pennsylvanian or younger and pre-Pleistocene time (Rene and Stanonis, 1995;Woolery, 2005).…”
Section: Introductionmentioning
confidence: 99%